Women Leadership: Examine the Capacity of Women as Leaders - Ahmad Muktamar B (Institute of Computer Science (IOCS), 2022)
This study describes women's leadership with a focus on studying the capacity of women as leaders. Aims to identify whether leadership is more effective and has better performance than male leadership. This type of research uses library research with analytic descriptive methods. The data in this study were obtained from books, journals, other reference websites related to the research topic. The approach used in this research is a feminist approach, where this approach tends to address gender issues, particularly those related to women's leadership. Another approach is the philosophical approach, as well as the historical approach. In this study it was found that women's leadership is related to feminine character. There are five attributes attached to feminine character, 1) Caring, 2) Vision, 3) Collaboration, 4) Courage, and 5) Intuition. It was also found that there are four factors that influence women's leadership, namely: Mother, Seductress, Pet and Iron Maiden. In addition, women's leadership is also supported by a transformational style and feminism. Meanwhile, women's success in leading is supported by feminist ethics, namely 1) Maternal Thinking, 2) Caring, and 3) Ethich of Care.